Congregational vitality – a perspective from Galatians - Tolmie, F. (Acta Theologica, 2024)
The aim of this study is to shed light on the development of “an ecclesiology from below” for our time from the Letter to the Galatians. For this purpose, Schoeman’s view of “an ecclesiology from below” is taken as point of departure, i.e., that it is “a theology lived and experienced in the faith community” (Schoeman 2020:102). To achieve this, the ecclesiology of the letter is scrutinised for aspects that might be relevant for faith communities in our time. The following aspects that might be relevant are identified and discussed: 1. God’s calling as the point of departure; 2. The centrality of the gospel; 3. The importance of “the hearing of faith”; 4. The role of ritual; and 5. The guidance of the Spirit.